The Power of Conferences: Stories of serendipity, innovation and driving social change - Deborah Edwards (UTS ePRESS, 2017)
With a focus on ten notable Australians, including Nobel Laureates Professor Barry Marshall and Professor Brian Schmidt, former Chief Scientist, Professor Ian Chubb, and Parliamentarian, the Honourable Linda Burney, The Power of Conferences explores the deep and lasting impact of conferences on the development and success of Australian luminaries. Each chapter features a reflection from a leader in Australian academia, politics, or community service, on the significant effects conferences have had on their personal and professional achievements. From chance encounters that result in the cultivation of new networks and collaborations to innovation and research breakthroughs, these leaders describe the conferences that have enabled them and others to go on to create real and lasting social change.